55. Minimally invasive lateral transpsoas approach: Comorbidity in our cases. Issue 12 (December 2016) - Stipa, G.; Frondizi, D.; Fanelli, C.; Gobbi, D.; Mazzetelli, P.; Chirico, A. Di; Carletti, S.
Abstract : The minimally invasive lateral transpsoas approach to the lumbar spine is a valid and recent alternative to interbody placement at levels L1–L5 in the setting of degenerative disc disease, spondylolisthesis, and scoliotic or kyphotic deformity. The benefits over traditional open surgery include reduced blood loss, decreased postoperative pain and narcotics use, shorter hospital length of stay, faster recover and quicker return to work and normal activity. The most common complications following this procedure include anterior thight numbness, lower extremity radiculopathy with weakness, iliopsoas and/or quadriceps weakness, and pseudoarthrosis. Papanastassiou et al. reported on two patients unusual complication of controlateral femoral nerve compression. The direct lateral approach requires the patient to be in lateral decubitus position. The technique utilizes specialized retractors allowing for direct visualization of the surgical approach corridor. Electrophysiological monitoring is believed to be critical in localizing the lumbosacral plexus during positioning of the retractor system. In according to the recent guidlines SINC-NeuroSIAARTI-SINCh, Intraoperative Stimulation (Clip and Probe), Free-Run EMG, PES and PEM of the both Legs are used. We monitorized 21 patients: 5 pazients had a postoperative temporary weakness of the Iliopsoas muscle, and only one patient with impaired diabete had a post operative spondilodiscitis.